951. Virtually the Same: Our Experience Teaching Abx Before and During the Pandemic. (4th December 2021) - Schafer, Katherine R; Shen, E; Peters, Timothy R
Abstract: Background: Understanding core principles of empiric antibiotic (abx) therapy is essential for abx stewardship. Pre-pandemic, the "Abx 101" workshop taught students an initial approach to empiric abx. Due to the pandemic, the session became virtual. We hypothesized that the face-to-face version (FTF) would be more effective and more positively reviewed by students compared to the virtual. Methods: For the FTF, 3 faculty facilitated workshops of 50 3rd year medical students. The intro reviewed the typical microbiota of body areas (or common pathogens for community-acquired disease in sterile spaces). Student small groups were assigned a category of abx coverage (e.g. "MRSA drugs"), and completed a worksheet to identify abx in the assigned category from a reference list of abx. Groups taught back to the class (jigsaw technique) about abx for their respective categories. Next, faculty facilitated a large group discussion in which they matched initial abx therapy for each body area's typical microbiome or pathogens. Finally, groups presented cases to the class and identified likely diagnosis, most likely organisms, and appropriate empiric abx to target those organisms. For the virtual version, the format was adapted for a 1 hour online interactive session with 1 MD facilitator, 20-25 students, and no breakout groups/jigsaw technique. The content was unchanged other than fewer cases. Results: 26 of 140 (19%) students completed the survey (n=13 FTF, n=13 virtual). An independent-samples t-test compared FTF and virtual overall satisfaction scores. There were no significant differences in satisfaction from the FTF (M=8.54, SD=1.04) and virtual sessions (M=8.62, SD=1.94); t(24)=-.126. p=0.901. 100% of both groups rated the session as quite/extremely relevant to their training and 100% of respondents in both groups deemed the format of the sessions appropriate for the content. In the FTF group, 76% of respondents felt the session was quite/extremely effective for learning about abx spectra of activity, compared to 69% in the virtual group ( X 2 (1, N = 26) = .195, p = .658). Conclusion: "Abx 101" was relevant, effective, and formatted well for learning about empiric abx, in FTF and virtual versions. These findings suggest that this curriculum is effective overall and adapts well for in-person and remote learning. Disclosures: All Authors : No reported disclosures